1996
DOI: 10.1080/095530096144509
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a vector containing a site-specific DNA double-strand break with 3-phosphoglycolate termini and analysis of the products of end-joining in CV-1 cells '

Abstract: Previous studies have shown that linearized SV40-based shuttle vectors transfected into mammalian cells are efficiently recircularized by an error-prone end-joining pathway. To determine whether and with what specificity free radical-mediated double-strand breaks are rejoined by this pathway, a structural mimic of such a break was introduced at a specific site in an SV40-based shuttle vector, by ligating purified 3'-phosphoglycolate-terminated oligonucleotides into 3' recessed ends generated in the linearized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…To generate internally labeled plasmid substrates, plasmid pRZ56 was linearized with MluI and then 10- and 11-base 5′-overhangs were formed by controlled 3′-resection with T4 DNA polymerase in the presence of dTTP (24). Construction of a vector containing a site-specific DNA double-strand break with 3′-phosphoglycolate termini and analysis of the products of end joining in CV-1 cells (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate internally labeled plasmid substrates, plasmid pRZ56 was linearized with MluI and then 10- and 11-base 5′-overhangs were formed by controlled 3′-resection with T4 DNA polymerase in the presence of dTTP (24). Construction of a vector containing a site-specific DNA double-strand break with 3′-phosphoglycolate termini and analysis of the products of end joining in CV-1 cells (24).…”
Section: Methodsmentioning
confidence: 99%
“…Construction of a vector containing a site-specific DNA double-strand break with 3′-phosphoglycolate termini and analysis of the products of end joining in CV-1 cells (24). An unlabeled 13-mer (5′pGCCGGACGCGACG) and a 5′-end-labeled 14-mer (5′*pCGAGGAACGCGACG) were ligated into the 10- and 11-base overhangs, respectively, and the plasmid was purified by agarose gel electrophoresis and electroeluted (25).…”
Section: Methodsmentioning
confidence: 99%
“…The modified oligomer was purified by gel electrophoresis and HPLC, and its structure verified by mass spectrometry (14). Internally labeled blunt-ended plasmid substrates were prepared by ligating this 5′- 32 P-labeled 11-mer, or an analogous 3′-hydroxyl 11-mer, into an 11-base 5′ overhang of plasmid pRZ56 and were purified by agarose gel electrophoresis as described (15,16). A substrate of identical sequence but with 3′-end label was generated by cutting circular pRZ56 with MluI, and filling in the 4-base 5′ overhang with dGTP and [α- 32 P]dCTP (3000 Ci/mmole, Perkin-Elmer), using exonuclease-deficient Klenow fragment.…”
Section: Methodsmentioning
confidence: 99%
“…Previous end-joining experiments employed an SV40-based shuttle plasmid (pSV56) designed to introduce a DSB in a polylinker in the intron of the T-antigen gene (9). However, because the presence of the SV40 origin reduces the yield of the plasmid from bacterial cultures, the polylinker region of pSV56 was excised as a 625-bp PflMI/AvrII fragment, and cloned into pBR322 between the EcoRV and NheI sites (the PflMI cut was blunt-ended with T4 polymerase).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure resects each 3′-terminal strand to the first thymine in the sequence, resulting in a 10-base 5′ overhang at one end and an 11-base 5′ overhang at the other. An unlabeled 13-mer and a 5′- 32 P-labeled 14-mer, each complementary to one of the 5′ overhangs, were successively ligated into the overhangs, to yield site-specifically labeled substrates with partially complementary (-ACG) overhangs, as described previously (9,10). Control experiments showed that the oligomers were ligated onto at least 90% of the overhangs (data not shown).…”
Section: Methodsmentioning
confidence: 99%